Analisis Pemanfaatan Teknologi Informasi dalam Meningkatkan Kualitas Pendidikan di Era Digital - Lela Budiarti; Alwendi; Andi Saputra Mandopa (SMART : Jurnal Teknologi Informasi dan Komputer, 2025)
Digital innovation is an important aspect in improving educational performance in the era of ever-evolving technology. This study aims to explore the impact of implementing a digital-based management system in improving school operational efficiency and the quality of education. The focus of the problem in this study is how the implementation of technology can improve various managerial aspects in the world of education, including administrative management, learning processes, and communication between educators, students, and parents. The use of Information Technology in education has become a key factor in improving the quality of learning in the digital era. This study aims to analyze how the application of ICT contributes to improving the quality of education, both in terms of learning methods, access to information, and the effectiveness of interactions between educators and students. The research methods used are literature studies and qualitative analysis of various ICT implementations in formal and non-formal education environments. The results of the study show that the use of ICT, such as e-learning platforms, digital learning applications, and educational social media, can enrich the learning process, increase learning motivation, and expand the reach of education to previously difficult-to-reach areas. However, challenges such as the digital divide, lack of teacher training, and limited infrastructure still need serious attention. Thus, optimal and sustainable ICT integration is needed to support the achievement of quality education in the digital era.